2020
DOI: 10.1186/s12884-020-03009-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the utilization of antenatal care among married women of reproductive age in the rural Thatta, Pakistan: findings from a community-based case-control study

Abstract: Background: There are differences in antenatal care (ANC) utilization between urban and rural areas of Pakistan. Although multiple factors have been studied affecting the utilization of general health care services, the effect of road network distance particularly on the utilization of ANC has not been assessed. Therefore, this study aimed to determine the association between road network distance from a health care facility and utilization of the ANC among women of reproductive age in Thatta Pakistan. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
7
16
0
Order By: Relevance
“…This figure is higher than the national level (59%) reported by ADHS in 2015 [ 5 , 6 ] and comparable with another study conducted in Kandahar province [ 27 ]. The rate of ANC utilization in the present study is consistent with those asserted in many studies conducted in other developing countries, such as Rwanda, Bangladesh, Jordan, and Ethiopia [ 7 11 , 18 , 23 ]. This finding epitomizes many developing countries where a substantial proportion of pregnant women fail to regularly make their ANC visits.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This figure is higher than the national level (59%) reported by ADHS in 2015 [ 5 , 6 ] and comparable with another study conducted in Kandahar province [ 27 ]. The rate of ANC utilization in the present study is consistent with those asserted in many studies conducted in other developing countries, such as Rwanda, Bangladesh, Jordan, and Ethiopia [ 7 11 , 18 , 23 ]. This finding epitomizes many developing countries where a substantial proportion of pregnant women fail to regularly make their ANC visits.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study, of which we are aware, to determine the magnitude of ANC services utilization and its determinants among women who had at least one delivery in the last two years in Kandahar city. The results of this community-based cross-sectional study were consistent with the findings of other pertinent studies conducted in developing countries [ 7 11 , 18 , 23 ]. We found that ANC utilization was highly associated with the educational status of the mother, pregnancy intention, and her place of residence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They cited the apathetic attitude of staff and poor service delivery as major reasons for avoiding these facilities. This finding is consistent with a national survey which reported that only 32.6% of patients attend public health facilities in Pakistan [23]. Different studies have also pointed out that private health facilities are preferred in Pakistan due to better facilities and quality of care [24][25][26].…”
Section: Individual Barrierssupporting
confidence: 89%
“…Despite this mounting evidence, no study to date has conducted an in-depth exploration of the multi-faceted barriers to maternal and newborn health service utilization in rural Pakistan. Previous studies have determined the rates of service utilization without exploring the sociocultural determinants of health-seeking behavior [22][23][24]. Addressing this gap, we designed this interpretive study to interact with both community members and health care providers to identify the multifaceted barriers to health service utilization in rural Pakistan.…”
Section: Introductionmentioning
confidence: 99%